2022
DOI: 10.3389/fpsyg.2022.845283
|View full text |Cite
|
Sign up to set email alerts
|

Self-Ascribed Paranormal Ability: Reflexive Thematic Analysis

Abstract: This study investigated personal perceptions (involvements) and comprehensions (interpretations) of self-ascribed paranormal abilities. Twelve participants with supposed supernatural powers took part in semi-structured interviews exploring the origin, phenomenology, and nature of their powers. Interview transcripts were analysed using reflexive thematic analysis (RTA), a qualitative method that identifies patterns within data. Four major themes expressed meanings and representations held by participants: Forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The potential psychological benefits of paranormal advocacy are not merely limited to belief and experience. In a recent study using reflexive thematic analysis, Drinkwater et al (2022a , b) found that justification of professed paranormal abilities created a sense of personal coherence and significance by providing a framework for structuring significant life events.…”
Section: Introductionmentioning
confidence: 99%
“…The potential psychological benefits of paranormal advocacy are not merely limited to belief and experience. In a recent study using reflexive thematic analysis, Drinkwater et al (2022a , b) found that justification of professed paranormal abilities created a sense of personal coherence and significance by providing a framework for structuring significant life events.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, these findings align with prior research, which reported that PB in the absence of cognitive-perceptual factors allied to psychopathology, was benign, or even in some instances beneficial to well-being [ 2 ]. For example, PB can perform adaptive psychological functions such as facilitate the development of self-concept [ 90 ], provide meaning [ 91 ], and create positive affect and reassurance [ 92 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…A useful starting point in this process would be to conduct interviews with believers exploring the nature, function, and consequences of their paranormal/illusory convictions. This approach has previously revealed the profound effect that personal paranormality (i.e., beliefs, perceived experiences, and professed abilities) have on individual sense of self and perceptions of well-being (Drinkwater et al, 2013(Drinkwater et al, , 2017a(Drinkwater et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%